PENGARUH SERVICE STANDARD COMMUNICATION DAN KOMITMEN MANAJEMEN TERHADAP KUALITAS LAYANAN DAN KEPUASAN PELANGGAN - Lulu Setiawati; Josephine Kurniawati Tjahjono (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. Nowadays competition has occured for different types of Industries, eithermanufacture or service Industries. Organization needs to have the right strategy to winthe the competition and sustain in the long run. Many people have increased theirawareness for health and at the same time the advance of technology was followed bythe high demand of society toward better health service, has became the foundation forthe management at the hospitals to make decision to improve their services. Thisreearch wanted to find out the effect of Service Standard Communication, ManagementCommitment towards Service Quality and Customer Satisfaction. The respondents arethose people who has had treatment at RSUD Dr. Soetomo. Data analysis wil be usingPartial Least Square (PLS). There was 100 respondents participating in this research.The result showed that Service Standard Communication, Management Commitmenthas effect on Service Quality and Customer Satisfaction. Pople who has visited thehospital felt satisfied with the service given by the hospital. Keywords: Service Standard Communication, Management Commitment, Service Quality,Customer Satisfaction